DESIGN AND FATIGUE ANALYSIS ON SUBSEA PIPELINE FREE SPAN IN JAVA SEA - Damar Dharmadi Prasidda, Satria
Indonesia is one of the world's leading oil and gas producers. In the BAU (Business As Usual) scenario from BPPT 2021, it is estimated that the national energy demand in 2019-2050 will continue to increase. One of the facilities used in the use of energy reserves is the subsea pipe. In this Final Project, the design and analysis of a subsea pipeline located in the Java Sea from land to a depth of 56 meters is carried out. In the design process, environmental data processing pipe wall thickness analysis, on-bottom stability analysis, installation analysis and free span analysis are required. There is also a follow-up analysis required to check the maximum allowable free span has met the design life (15 years) using fatigue analysis. In this Final Project, environmental data processing is carried out using the Kolmogorov-Smirnov distribution test using normal, lognormal, and Gumbel distribution theories. The design and analysis refer to the standard codes DNVGL-ST-F101, DNVGL-RPF109, DNVGL-RP-F114, DNVGL-RP-F105, and DNVGL-RP-C203. In the environmental data processing, significant wave height, wave crest period, current speed, 90% water depth, maximum storm surge, and minimum storm surge at 1-year, 10-year, and 100-year return periods were obtained. In the pipe wall thickness analysis, a minimum subsea pipe wall thickness value of 12.7 mm was obtained. In the on-bottom stability analysis, a minimum concrete layer wall thickness of 52 mm was obtained and using trenching with a trenching angle of 45° with a depth of zone 1 to zone 4 of 0.53 meters, 0.13 meters, 0.103 meters, and 0.094 meters, respectively. In the installation analysis, a suitable configuration has been obtained in the static and dynamic installation of pipes at a minimum water depth of 20 meters to a maximum water depth of 56 meters. In the free span analysis, it has been found that the maximum free span length in zone 1 to zone 4 is 12.93 meters, 14.27 meters, 15.13 meters, and 15.17 meters, respectively. In addition, in the fatigue analysis, it can be concluded that the free span length will predominantly get longer as the gap between the subsea pipe and the seabed gets smaller.